(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objectives: To create, on the basis of the International Classification of Nursing Practice (ICNP®), nursing diagnoses/outcomes and interventions statements in the care of people with intestinal elimination stoma and confirm, with specialists, the pertinence and relevance of the statements created. Methods: Methodological research developed from September 2016 to January 2017, in which negative, positive, risk and chance nursing diagnoses/outcomes were created and statements of interventions for each diagnostic/outcome. The diagnoses/outcomes and interventions created were mapped with the ICNP® version 2015, resulting in constant statements not included in the classification. The statements created and mapped were submitted to the process of confirmation of pertinence and relevance by 10 specialists, through a virtual questionnaire and data analysisby the percentage agreement method. Results: 110 nursing diagnoses/outcomes were created, of which 78 (70.9%) were confirmed by specialists and 119 nursing interventions, of which 103 (86.5%) were confirmed. Conclusion: the creation of statements of nursing diagnoses/outcomes and interventions and the process of confirmation of pertinence and relevance by specialists helped in the search for evidence of elements of nursing practice directed to the specific clientele.